Dispensing Prescription Medicines without a Prescription in Pharmacy - M. Rifqi Rokhman; Mentari Widiastuti; Satibi Suwarni; Ria Fasyah Fatmawati; Ni'matul Munawaroh; Yenda Ayu Pramesti (Faculty of Pharmacy, Universitas Gadjah Mada)
A poor drug monitoring system in many developing countries makes patient easy to buy any prescription medicines without prescription. This research aimed to assess the compliance of pharmacy towards prescription medicine’s regulations, pharmacist knowledge toward a list of medicines as prescription or over the counter medicines, and the reasons associated with dispensing prescription medicines without a prescription in pharmacy. The research was a descriptive non-experimental study. The sample was taken using simple random sampling in Sleman and Kota Yogyakarta Regency from September 2016 to January 2017. Data were taken in 2 steps, using simulated patient and a questionnaire one week after the first step. The simulated patient would come to the pharmacy and requested amlodipine 5 mg 10 tablets and allopurinol 100 mg 20 tablets. The questionnaire assessed pharmacist knowledge in classifying of several medicines as prescription or over the counter medicines, information taken and given when dispensing prescription medicines without a prescription, and the reason associated with dispensing prescription medicines without a prescription. The data were analyzed descriptively. The results showed that from 138 pharmacies randomly selected, 132 pharmacies (95,7%) dispensed amlodipine and 127 pharmacies (92,0%) sold allopurinol without a prescription. Majority of pharmacists (more than 85%) hold a view that prescription medicines mainly for chronic diseases (glibenclamide, metformin, amlodipine, captopril, allopurinol, dan simvastatin) as the over the counter medicines, as the main reason was patients regularly taking this medication before. However, the majority of pharmacists (79,2%) perceived that antibiotics as prescription medicines that should be dispensed only with a medical prescription. This research showed that pharmacist does not fully implement applicable regulations.